The Influence of Technology and Information on Student’s Behavior: a Case Study of SMA Negeri 1 of Pantai Cermin at Serdang Bedagai - Suwardi Lubis; Riza Buana (Britain International for Academic Research (BIAR) Publisher, 2020)
The progress of information technology is very influential in life. The changing of student’s behavior will be seen clearly now days than before. Apart from all kinds of controversies. This case full of controversies, but the students could not be separated from technology and the internet. The internet itself has a negative effect and positive effect. Human’s interaction also can be change unconditionally. This technology, specially in communication and media have shown a new page in daily life and influence the social life and social behavior. This research is aimed to know the purpose of the information technology and communication to support the student’s development effectively and efficiently and to know how the student’s social behavior and the effect of using information technology and communication to the student’s social behavior in SMA N 1 Pantai Cermin. The results of this research showed that mobile phone and the internet as a form of technological development had positive and negative impacts on the cognitive development and moral behavior of students. The positive impact of using mobile phones is the most effective and efficient communication tool and also the media for accessing information related to education.